Edukacja jako zadanie otwarte. Edukacja do samodzielności. Warsztaty z dociekań filozoficznych. Teoria i metodyka Aldony Pobojewskiej wsparciem metodycznym w kryzysie edukacji - Skrzypczak, Alicja (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
The publication of Aldona Pobojewska Edukacja do samodzielności. Warsztaty z dociekań filozoficznych. Teoria i metodyka is an important work, supporting educator’s theoretical workshop and practice, that offers an original method of “workshop in philosophical inquiry” (WDF) embedded in Matthew Lipman’s philosophy and in his project Philosophy for Children. The method targets education to specific current problems of the social world, including the ethical world, and indicates the need for the development of social competencies via discussion and for the shaping of autonomy attitude, both moral and intellectual. Interdisciplinary character of WDF method allows the reader and the person leading the class to accept various perspectives: philosophical, psychological and pedagogical. However, as the author claims, the philosophical perspective is the one exposed the most in the publication. WDF is used for initial reflection on general problems associated with a given discipline and for strengthening competencies that constitute the future intellectual capital. It is the answer for the question of a possibility of escaping the current education crisis, the encouragement to express opinions on the expectations towards contemporary education and the way of participating in decisionmaking process concerning its shape. Therefore, the aim of the method is responsibility founded on participation and mutual trust as well as on conscious development of key competencies in the process of self-determination.